Asymmetric changes of growth and reproductive investment herald altitudinal and latitudinal range shifts of two woody species. (4th August 2014) - Matías, Luis; Jump, Alistair S.
Abstract Ongoing changes in global climate are altering ecological conditions for many species. The consequences of such changes are typically most evident at the edge of the geographical distribution of a species, where range expansions or contractions may occur. Current demographical status at geographical range limits can help us to predict population trends and their implications for the future distribution of the species. Thus, understanding the comparability of demographical patterns occurring along both altitudinal and latitudinal gradients would be highly informative. In this study, we analyse the differences in the demography of two woody species through altitudinal gradients at their southernmost distribution limit and the consistency of demographical patterns at the treeline across a latitudinal gradient covering the complete distribution range. We focus on Pinus sylvestris and Juniperus communis, assessing their demographical structure (density, age and mortality rate), growth, reproduction investment and damage from herbivory on 53 populations covering the upper, central and lower altitudes as well as the treeline at central latitude and northernmost and southernmost latitudinal distribution limits. For both species, populations at the lowermost altitude presented older age structure, higher mortality, decreased growth and lower reproduction when compared to the upper limit, indicating higher fitness at the treeline. This trend at the treeline was generally maintained through the latitudinal gradient, but with a decreased growth at the northern edge for both species and lower reproduction for P. sylvestris. However, altitudinal and latitudinal transects are not directly comparable as factors other than climate, including herbivore pressure or human management, must be taken into account if we are to understand how to infer latitudinal processes from altitudinal data.